Catching season and supply chain fishery resources (Holothuroidea sp) small scale on Sapuka Island Pangkep Regency South Sulawesi (Agrikan Jurnal Agribisnis Perikanan, 2022)
One of the fishery commodities included in the leading fishery commodity is the sea cucumber (Holothuroidea sp.). Sea cucumber is a target for anglers' catches because it has high economic value and can be easily marketed, not only on a local scale but also for export. The increased demand for sea cucumber exports can threaten the sustainability of sea cucumber resources in nature. This is due to the effect of fulfilling market demand directly related to fishing efforts by fishers. Responding to these problems, the purpose of this study was to analyze the fishing season and the supply chain of sea cucumbers on Sapuka Island, Pangkep Regency, South Sulawesi Province. The research methods used are the survey, observation, and Participatory Rural Approach (PRA). There were 20 PRA participants, including 10 sea cucumber fishers, 2 village government officials, 3 community members, 2 community groups (POKMAS), and 3 sea cucumber collectors. The data that has been collected is then analyzed using MDS using the Rapfish approach. The results showed that the sea cucumber fishing season on Sapuka Island was throughout the year January-December, with the highest fishing season in January-April. There are 5 models/patterns in the sea cucumber supply chain on Sapuka Island, namely the sea cucumber flow; 1) Sapuka Island fishermen-exporters in Makassar, 2) fishermen-collectors in Makassar-exporters in Makassar, 3) fishermen-collectors in Galesong-Exporters in Makassar, 4) fishermen-Sapuka Island collectors-Exporters in Makassar, 5) fishermen-collectors of Sapuka-collectors of Galesong-Exporters in Makassar.
Keywords: Holothuroidea sp; Catching Season; Supply Chain; Sapuka Island; Pangkep Regency